Penerapan Model Pembelajaran Inkuiri Terbimbing Berbantuan Software Electronics Workbench untuk Meningkatkan Hasil Belajar Ranah Kognitif Peserta Didik Kelas XII pada Materi Pokok Kelistrikan Arus Searah di SMAN 1 Lasolo - Yusnanita, Yusnanita; Erniwati, Erniwati; Yuris, Muh. (Jurusan Pendidikan Fisika, 2020)
The guided inquiry learning model is an approach that involves students actively thinking and finding what they want to know. This research have as a purpose to knowladge cognitive learning outcomes of students taught by guided inquiry learning models assisted by electronic workbench software. The population in this research were students of class XII MIA SMAN 1 Lasolo registered in the odd semester of the 2019/2020 academic year consisting of 3 classes with 104 students. Samples were taken by purposive sampling technique so that class XII MIA1 was obtained as an experiment class and class XII MIA2 as a control class. Data collection techniques for students' cognitive learning outcomes using multiple choice tests. Data analysis uses descriptive analysis and inferential statistics. Based on the results of data analysis and discussion obtained: (1) there is no significant difference between the average value of the experiment class pretest and the control class before learning; (2) there is a significant difference between the average value of cognitive class learning outcomes of the experiment class and the control class; (3) the average value of N-Gain learning outcomes of the cognitive domain of experiment class students is in the high category with the acquisition of a value of 0.73 while the average value of the N-Gain of the control class is in the moderate category of 0.49. This shows that the guided inquiry learning model assisted by electronics workbench software is very suitable to be applied in physics learning activities in schools.